2003
DOI: 10.1614/p2002-014
|View full text |Cite
|
Sign up to set email alerts
|

Weed management with CGA-362622 in transgenic and nontransgenic cotton

Abstract: Field studies conducted at three locations in North Carolina in 1998 and 1999 evaluated crop tolerance, weed control, and yield with CGA-362622 alone and in combination with various weed management systems in transgenic and nontransgenic cotton systems. The herbicide systems used bromoxynil, CGA-362622, glyphosate, and pyrithiobac applied alone early postemergence (EPOST) or mixtures of CGA-362622 plus bromoxynil, glyphosate, or pyrithiobac applied EPOST. Trifluralin preplant incorporated followed by (fb) fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 34 publications
6
31
1
1
Order By: Relevance
“…Prickly sida was controlled 93 to 99% with either glyphosate formulation, with no difference in control between formulations ( Table 2). As reported by other researchers (Porterfield et al 2002a(Porterfield et al , 2003, our data also indicate that trifloxysulfuron did not control prickly sida. As expected, prickly sida control with either glyphosate formulation was not improved by the addition of trifloxysulfuron.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Prickly sida was controlled 93 to 99% with either glyphosate formulation, with no difference in control between formulations ( Table 2). As reported by other researchers (Porterfield et al 2002a(Porterfield et al , 2003, our data also indicate that trifloxysulfuron did not control prickly sida. As expected, prickly sida control with either glyphosate formulation was not improved by the addition of trifloxysulfuron.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, trifloxysulfuron injured cotton 7 to 24%, depending on location. This level of injury to cotton in North Carolina and Virginia is not uncommon (Crooks et al 2003;Porterfield et al 2003;Richardson et al 2004aRichardson et al , 2004b. Injury was visually apparent as a chlorosis, discoloration of treated cotton foliage (7 to 18%), and stunting (2 to 6%) (data not shown).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The main effect of trifloxysulfuron rate was not significant (P 5 0.0575), and trifloxysulfuron at the higher rate reduced Palmer amaranth fresh weight only 25%. Trifloxysulfuron is typically effective on Palmer amaranth (Branson et al 2005;Porterfield et al 2003), but the populations used in this experiment were likely resistant to ALS-inhibiting herbicides, such as trifloxysulfuron. Earlier research has shown that trifloxysulfuron was not effective in controlling GR and GS Palmer amaranth accessions from Arkansas when applied at manufacturer's suggested field rate (Norsworthy et al 2008).…”
Section: Experiments 2 Efficacy Of Herbicides Against Palmermentioning
confidence: 99%
“…Reconhecendo-se o potencial de prejuízo à cultura do algodoeiro, atualmente espécies de Amaranthus são consideradas problema em campos de produção de algodão no Paquistão (Bukun, 2005), na Austrália (Walker et al, 2005) e nos Estados Unidos (Troxler et al, 2002;Porterfield et al, 2003;Murdock et al, 2004;Richardson et al, 2007). No Brasil, estas espécies ocorrem em todos os Estados, com maior concentração em regiões agrícolas (Kissmann e Groth, 1999).…”
Section: Introductionunclassified